Condominium governance and law in global urban context - Lippert, Randy K., 1966-; Treffers, Stefan (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines condominium, property, governance, and law in international and conceptual perspective and reveals this urban realm as complex and mutating. Condominiums are proliferating the world over and transforming the socio-spatial organization of cities and residential life. The collection assembles arguably the most prominent scholars in the world currently working in this broad area and situated in multiple disciplines, including legal and socio-legal studies, political science, public administration, and sociology. Their analyses span condominium governance and law on five continents and in nine countries: United States (US), China, Australia, the United Kingdom (UK), Canada, South Africa, Israel, Denmark, and Spain. Neglected issues and emerging trends related to condominium governance and law in cities from Tel Aviv to Chicago to Melbourne are discerned and analyzed. The book pursues fresh empirical inquiries and cogent conceptual engagements regarding how condominiums are governed through law and other means. It includes accounts of a wide range of governance difficulties including chronic anti-social owner behaviour, short-term rentals, and even the COVID-19 pandemic, and how they are being dealt with. By uncovering crucial cross-national commonalities, the book reveals the global urban context of condominium governance and law as empirically rich and conceptually fruitful. The book will appeal to researchers and students in socio-legal studies, law, sociology, political science, urban studies, and public administration as well as journalists, social activists, policy makers, and condo owners/board members"--
Introduction : condominium governance and law in global urban context / Randy K. Lippert and Stefan Treffers -- (United Kingdom) Narratives of property and the limits of legal reform in the English leasehold system and its counterparts in other jurisdictions / Sarah Blandy -- (Canada and Australia) Embedded property / Douglas C. Harris -- (US and Australia) Private governance of condominium land : common law versus statute / Cathy Sherry -- (Canada and the US) Turnover or roll over? : property developer legal avoidance and influence on condominium governance in New York City and Toronto / Randy K. Lippert and Stefan Treffers -- (Israel) Between ownership and privacy : private surveillance and condominium governance in Israel / Dorit Garfunkel -- (China) Homeowner associations' role in China's condominium governance / Lisa Wei Gao -- (Australia) Living with strata towers : a case study of metropolitan Melbourne in disruptive global times / Rebecca Leshinsky -- (South Africa and European Countries) European and South African law perspectives on the efficacy of sanctions to confront chronic rule breakers in condominium developments / Cornelius van der Merwe -- (Denmark) Untying built-in knots in Danish condominium law : a balancing of interests / Kristian Graven Nielsen and Hans Henrik Edlund -- (Spain) New challenges to Spanish condominiums in an economic and pandemic crisis / Sergio Nasarre-Aznar (University Rovira i Virgili) -- (Australia) Law reform challenges : an evaluation of Australia's strata law trends and implications / Nicole Johnston -- (Canada and US) The emerging architecture of state regulation in North American condominium governance / Stefan Treffers -- (Australia) Condominiums aren't forever : Governance, redevelopment, and implications for the city / Hazel Easthope and Bill Randolph -- (China) Law on paper and law in practice : the contradictions of condominium governance in urban China / Ngai Ming Yip, Yang Zheng, and Sheng Jiang -- (US) Chicago's "deconversion" waves and the fragility of condominium associations / Evan McKenzie -- Conclusion : condominium Governance and Law, Property, and Global Urban Futures.
OCLC-licensed vendor bibliographic record.
Keywords: Condominiums -- Law and legislation; Condominium associations -- Law and legislation; Homeowners' associations -- Law and legislation; ARCHITECTURE / Domestic; ARCHITECTURE / Urban & Land Use Planning; BUSINESS & ECONOMICS / Business Law